Basic and clinical studies of gatifloxacin in dental and oral surgery - Shiiki, Kazuo; Deguchi, Koichi; Yamamoto, Tadashi; Ohno, Tomoya; Kanno, Kazuyuki; Matsui, Yoshiro; Yamane, Nobuo; Sasaki, Jiro; Michi, Kenichi; Sakamoto, Haruo (Japanese Journal of Chemotherapy, 1999)
We performed experimental and clinical studies with gatifloxacin (GFLX), a new synthetic antimicrobial agent for oral use, in the field of oral surgery. 1. GFLX, at 100mg, was administered orally to 10 patients, and its concentration in maxillary bone ranged from 0.35 to 0.80 peg at 1.75 to 5.5 hours in 4 subjects, in mandibular bone from not detectable to 1.85μg/g at 3.25 to 5 hours in 4 subjects, in maxillary alveolar bone was 0.37μg/g at 2.75 hours in 1 subject, and in mandibular alveolar bone was 0.45μg/g at 3 hours in 1 subject. 2. GFLX, at 100mg, was administered orally to 2 patients, and the concentrations in exudate during the operation ranged from 0.49 to 0.57μg/g at 2.83 to 4.17 hours after administration. 3. A clinical study was conducted in 104 patients with periodontitis, pericoronitis and osteitis of the jaw. The efficacy rate, judged by doctors, was 96.8% for 93 patients, whereas the comparative score evaluation was 93.4% for 91 patients. 4. Three hundred and thirteen strains of organisms were isolated from closed abscesses, and the bacteriological eradication rate was 100% in all strains. 5. Side effects were observed in 3 cases (diarrhea and rash etc.). Abnormal laboratory findings were recognized in 12 cases (increased S-GOT, S-GPT levels and eosinophil count etc.). From these results, we conclude that GFLX is a useful antimicrobial agent for the treatment of odontogenic infections at the dose of 200 or 400mg/day.